2019
DOI: 10.1111/cpr.12718
|View full text |Cite
|
Sign up to set email alerts
|

Pentamidine inhibits prostate cancer progression via selectively inducing mitochondrial DNA depletion and dysfunction

Abstract: Objectives We investigated the anti‐cancer activity of pentamidine, an anti‐protozoal cationic aromatic diamidine drug, in prostate cancer cells and aimed to provide valuable insights for improving the efficacy of prostate cancer treatment. Materials and methods Prostate cancer cell lines and epithelial RWPE‐1 cells were used in the study. Cell viability, wound‐healing, transwell and apoptosis assays were examined to evaluate the influences of pentamidine in vitro. RNA‐seq and qPCR were performed to analyse ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…Scaffold-based small molecule libraries are well poised to provide important insights for emerging targets such as the MALAT1 triple helix, as these libraries enable strategic tuning of relevant small molecule properties. For example, the para -substituted diphenylfuran (DPF) diamidine called furamidine, which originates from the promiscuous nucleic acid binder pentamidine ( 24–27 ), has known literature precedence for binding to a variety of nucleic acid structures and has enabled structure–activity relationship studies for therapeutically relevant RNAs ( 28–32 ). Importantly, the affinity and selectivity of DPF derivatives for nucleic acids can be modulated through varying amidine positioning and substituent incorporation through the amidine moieties ( 28 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“…Scaffold-based small molecule libraries are well poised to provide important insights for emerging targets such as the MALAT1 triple helix, as these libraries enable strategic tuning of relevant small molecule properties. For example, the para -substituted diphenylfuran (DPF) diamidine called furamidine, which originates from the promiscuous nucleic acid binder pentamidine ( 24–27 ), has known literature precedence for binding to a variety of nucleic acid structures and has enabled structure–activity relationship studies for therapeutically relevant RNAs ( 28–32 ). Importantly, the affinity and selectivity of DPF derivatives for nucleic acids can be modulated through varying amidine positioning and substituent incorporation through the amidine moieties ( 28 , 31 ).…”
Section: Introductionmentioning
confidence: 99%
“… 12 As well, pentamidine has been reported as a potent agent to inhibit prostate cancer progression by targeting mitochondria. 7 In addition, in nude mice xenograft experiments, pentamidine is able to dramatically reduce the growth of WM9 human melanoma and M47 Lewis lung carcinoma tumors. 12 , 13 , 15 These studies indicate the potential application of pentamidine in chemotherapy.…”
Section: Discussionmentioning
confidence: 99%
“…Pentamidine is a positively charged aromatic diamine that has a long history of its involvement in the clinical treatment of African trypanosomiasis, antimonial-resistant leishmaniasis and babesiosis as well as the prophylaxis of pneumocystis carinii pneumonia in acquired immune deficiency syndrome (AIDS) patients for several decades. 7–11 Recently, several reports suggested that pentamidine has antitumor potential. In fact, pentamidine has been shown to have anti-proliferative effects on various human cancer cell types such as melanoma, prostate, ovarian, colon, breast, lung, and cervical cancers in vitro.…”
Section: Introductionmentioning
confidence: 99%
“…Diamidines are believed to be minor groove binders and as such bind to the DNA double helix, particularly targeting AT-rich sequences [16][17][18][19], impeding replication and transcription processes in the kinetoplast and/or nucleus. Usually, they accumulate strongly in the trypanosome's single mitochondrion (and mitochondria of cancer cells [20]), the compartmentalisation of these dications being driven by the mitochondrial membrane potential and binding to the kinetoplast DNA (kDNA) (for a schematic of the trypanosome structure, see figure 2). Indeed, fluorescent diamidines light up the kinetoplast within 1 minute of administration, a process that is much delayed in resistant parasites [21].…”
Section: Diamidinesmentioning
confidence: 99%
“…Further development to an active (and colourless!) trypanocide was undertaken by Maurice Nicolle and Felix Mesnil at the Institut Pasteur [111] in collaboration with by Wilhelm Röhl and Bernhard Heymann at Bayer [7], who via Afridol Violet (20), the first of the symmetrical ureas of the series, and after synthesis of >1000 of related structures, found 'Bayer 205' in 1916 [112]. This was introduced clinically under the name Germanin, and the formula was kept secret and supplied only to German clinicians, i.e., in German colonial territories [113,114].…”
Section: Suraminmentioning
confidence: 99%